Dravyaguṇavijñāna - Gogaṭe, Vishṇū Mahādeva (Vidyāpīṭha Granthanirmitī Maṇḍaḷāsāṭhī Kôṇṭineṇṭala Prakāśana, 1982)
Materia medica of ayurveda.
Includes index.
In Marathi.
Materia medica of ayurveda.
Keywords: Medicine, Ayurvedic. / http://id.loc.gov/authorities/subjects/sh85083119; Materia medica / India. / http://id.loc.gov/authorities/subjects/sh2010100938